Analysis of Plant Growth and Yield in Varieties of Tomato (Solanum lycopersicum L.) Grafted onto Different Eggplant Rootstocks - Evy Latifah; Amik Krismawati; Mohammad Saeri; Zainal Arifin; Bas Warsiati; Dwi Setyorini; Paulina Evy Retnaning Prahardini; Herman Subagio; Donald Sihombing; Sri Satya Antarlina; Eko Widaryanto; Ariffin; et al. (International Journal of Agronomy)
This study aimed to examine plant growth of tomato grafted onto different eggplant rootstocks. We applied a randomized block design comprising twelve treatments with three replicates. Three varieties of tomato—Cervo, Karina, and Timoty—and three rootstocks—Gelatik, EG203 line, and Solanum torvum—were selected for this study. Nongrafted tomato plants of the same varieties were used as controls. The variables recorded were the number of branches, the diameter of scions and rootstocks, root length, and root dry weight at 4, 6, 8, and 10 weeks after planting (WAT) and relative growth rate, specific leaf area, and net assimilation rate at 4, 8, and 12 WAT. Grafted tomato plants demonstrated better growth than controls. There was a significant relationship between yield, plant growth parameters, and photosynthetic organs, expressed by higher production, greater scion diameter, longer roots, and increased relative growth rate, leaf area ratio, and net assimilation rate of grafted plants, compared to the controls.